THE EFFECT OF CHOCOLATE BISCUIT AND JELLY CANDY CONSUMPTION ON SALIVARY pH IN ELEMENTARY STUDENTS : Pengaruh Konsumsi Biskuit Coklat Dan Permen Jelly Terhadap pH Saliva Pada Siswa SD - Putu Widani; Putu Yetty Nugraha; I Gede Andhika Wiguna Aryana (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Dental caries is a disease of hard dental tissue, namely enamel, dentin, and cementume caused by a microorganism in a carbohydrate that can be shared. Stimulus secretion of saliva consists of mechanical stimulation including talking, chewing, and gargling, while chemical stimulation in the form of the impression of taste. Chocolate biscuits and jelly candies are sweet, sticky, and chewy cariogenic foods that greatly affect changes in salivary pH. Children aged 9-10 years are more susceptible to dental disease because it is a critical age group, at that age there is a transition of tooth growth from baby teeth to permanen teeth. Purpose: This study aims to determine the differences in salivary pH between consuming chocolate biscuits and jelly candies in students aged 9-10 years. Materials and Methods: The research design used was a pre-experimental study with a pretest and posttest control group design. The number of subjects required was 32 respondents, by taking a Simple Random Sampling, which was divided into 2 groups, each group consisting of 16 people. Data analysis used the Wilcoxon test and One Way ANOVA. Result and Discussion: The result showed that, the mean value of saliva pH before chewing chocolate biscuits was 8.09, in minute to five was 3.96, in minute to ten was 6.50, then in minute to fifteen was 7.33. While the mean salivary pH before chewing jelly candy was 7.66, in minute to five was 5.17, in in minute to ten was 6.81, and in minute to fifteen was 7.50. Conclusion: The conclusion of this study was that chewing chocolate biscuits was more influential in lowering salivary pH than chewing jelly candies after 5 (five) minutes of mastication and there was no difference in mean increase in salivary pH between groups after 10-15 (ten-fifteen) minutes of chewing chocolate biscuits and jelly candies.